Cloning of the RNA m6A Methyltransferase 3 and Its Impact on the Proliferation and Differentiation of Quail Myoblasts - Jing Liu; Wentao Zhang; Wei Luo; Shuibing Liu; Hongxia Jiang; Sanfeng Liu; Jiguo Xu; Biao Chen (Veterinary Sciences, 2023)
Methyltransferase 3 (METTL3), which has been demonstrated to play a crucial role in a variety of biological processes, is the key enzyme for catalyzing m6A modification in RNA. However, the complete protein sequence of METTL3 in quail has not been annotated, and its function in skeletal muscle of quails remains unknown. In the current study, the full-length coding sequence of the quail METTL3 was obtained through the 3′ rapid amplification of cDNA ends (3’ RACE) and its homology with that of other species was predicted based on a generated phylogenetic tree. A Cell Counting Kit-8 assay and flow cytometry in a quail myoblast cell line (QM7) demonstrated that METTL3 promotes myoblast proliferation. The overexpression of METTL3 in QM7 cells significantly increased the expression levels of the myoblast differentiation markers myogenin (MYOG), myogenic differentiation 1 (MYOD1), and myocyte enhancer factor 2C (MEF2C), further demonstrating that METTL3 promotes myoblast differentiation. Additionally, transcriptome sequencing following METTL3 overexpression revealed that METTL3 controls the expression of various genes involved in RNA splicing and the regulation of gene expression, as well as pathways such as the MAPK signaling pathway. Taken together, our findings demonstrated that METTL3 plays a vital function in quail myoblast proliferation and differentiation and that the METTL3-mediated RNA m6A modification represents an important epigenetic regulatory mechanism in poultry skeletal muscle development.